The The Investigation of Mercury in an Abandoned Artisanal and Small-Scale Gold Mining (ASGM) - Nicko Widiatmoko S.Si., M.Si.; Noviarso Wicaksono; Yeni Novitasari; R Arif Suryanegara; Nurohmat, Asep Nurohmat; Noor, Mochamad Rifat (Universitas Pendidikan Ganesha, 2024)
This paper Mercury in artisanal and small-scale gold mining (ASGM) is a major environmental and health issue. Since mercury in the environment is persistent, mapping and investigating mercury in abandoned ASGM areas is urgent to mitigate and minimize mercury pollution. This research was conducted to map and explore the presence of mercury in abandoned ASGM in Kalirejo Village, Kulon Progo District of Yogyakarta. Field exploration has shown that the abandoned ASGM were in a riverside area, close to settlement, surrounded by farming and plantations. Mercury analysis using the thermal decomposition method showed that four of five sediment samples contained Hg above 0.3 mg/kg, which indicated that the sediments at the four sampling points were contaminated. Mercury analysis using ICP OES spectrometry showed that three of six surface water samples contained Hg above 0.005 mg/L, indicating that Hg contaminated the surface waters at the three sampling points. Because the abandoned ASGM is close to residential areas, the riverside, and surrounded by community farming and plantation areas, residents may be exposed to mercury.